2013
DOI: 10.1088/0963-0252/22/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

On sheath energization and Ohmic heating in sputtering magnetrons

Abstract: In most models of sputtering magnetrons, the mechanism for energizing the electrons in the discharge is assumed to be sheath energization. In this process, secondary emitted electrons from the cathode surface are accelerated across the cathode sheath into the plasma, where they either ionize directly or transfer energy to the local lower energy electron population that subsequently ionizes the gas. In this work, we present new modeling results in support of an alternative electron energization mechanism. A mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
139
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(150 citation statements)
references
References 26 publications
11
139
0
Order By: Relevance
“…When interacting, energy is transferred from hot electrons, providing a positive feedback to cause even more ionization at that location. However, in very recent work by Hou et al 18 it was shown that heating by secondary electrons is not the dominant mechanism of power dissipation in magnetrons. Rather, plasma electrons are predominantly "energized" by Ohmic heating in the magnetic presheath, where the electron cross-field current density is high and the electric potential gradient is still large.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…When interacting, energy is transferred from hot electrons, providing a positive feedback to cause even more ionization at that location. However, in very recent work by Hou et al 18 it was shown that heating by secondary electrons is not the dominant mechanism of power dissipation in magnetrons. Rather, plasma electrons are predominantly "energized" by Ohmic heating in the magnetic presheath, where the electron cross-field current density is high and the electric potential gradient is still large.…”
mentioning
confidence: 98%
“…Additional local Ohmic heating, of roughly the same order of magnitude, is caused by electrons experiencing a potential drop in the z-direction, 18 i.e. when escaping the closed drift and forming plasma flares.…”
mentioning
confidence: 99%
“…It was therefore proposed 9,11 that the generation of doubly and higher charged ions must be critical to HiPIMS operation. An new mechanism, recently presented by Huo et al, 12 greatly reduces or even eliminates the need for secondary electrons. Using a global model of the magnetron discharge, Huo et al 12 showed that the voltage drop in the magnetic presheath can lead to very significant energy dissipation and electron heating.…”
mentioning
confidence: 99%
“…Electrons gain energy as they diffuse to magnetic field lines where the potential is higher. 12 In this contribution, the idea of presheath heating of electrons 12 is examined on a local level, and it is shown that there is a interdependence between presheath heating of electrons, the formation (and disappearance) of ionization zones 2-4 (a.k.a. spokes 11,16,17 ), and associated potential humps.…”
mentioning
confidence: 99%
“…Two areas of performance improvement are being developed in the MS technology. The first one is based on an increase in the degree of ionization of the sputtered flux [1][2][3][4][5][6][7], the second one is based on an increase in the temperature of the target surface up to the melting temperature [8][9][10][11][12][13]. The methods that ensure a high degree of ionization of sputtered atoms are called ionized physical vapor deposition (IPVD) [1].…”
mentioning
confidence: 99%